The relationship between staff development, organizational policy, staff welfare to personnel performance - Musalli, Naziru Mohammed; Harun, Azhar; Zainnudin, Ruslam (MCSER Publishing, Rome-Italy, 2015)
Nigeria Immigration Service (NIS) is one of the most important agency tight with the responsibility of Border management, Although the agency perform many functions other than patrolling borders ranging from issuance of e- passport and visa as well as checking travellers document.The organization played a significance role in controlling movement of illegal immigrants and other organised criminal activities in border zones.As border management become a central issue of concern in the contemporary global arena.In spite of the existence of many agencies of border management, still it is confronted with a lot of challenges as a result of increasing flows of people, goods and services across regional borders.The porosity of Nigerian borders coupled with manpower challenges that can properly mount the border affect the economic growth in the country.Massive influx of illegal immigrants with proliferation light arms and many form of contraband goods organized criminal activities, affect national security and economic development in Nigeria especially in the north/eastern part of the country as focal area of this study considerable number of questionnaires was distributed in the field and the data was analysed quantitatively using PLS Statistical package. In the conclusion this study suggestions would be given more concern of investigating a proper way to improve the performance of personnel in Nigeria Immigration Service (NIS) in order to achieve the purpose of this study. © 2015, Mediterranean Center of Social and Educational Research. All rights reserved.